2005
DOI: 10.1038/sj.emboj.7600789
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ cooperates with RB:E2F to implement RasV12-induced cellular senescence

Abstract: In primary cells, overexpression of oncogenes such as RasV12 induces premature senescence rather than transformation. Senescence is an irreversible form of G1 arrest that requires the p19ARF/p53 and p16INK4a/pRB pathways and may suppress tumorigenesis in vivo. Here we show that the transcription factor C/EBPβ is required for RasV12‐induced senescence. C/EBPβ−/− mouse embryo fibroblasts (MEFs) expressing RasV12 continued to proliferate despite unimpaired induction of p19ARF and p53, and lacked morphological fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
163
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(180 citation statements)
references
References 62 publications
15
163
2
Order By: Relevance
“…Inhibition of E2F transcription factors by Rb is an important pro‐senescence process (Mallette, Goumard, Gaumont‐Leclerc, Moiseeva & Ferbeyre, 2004; Narita et al., 2003; Sebastian, Malik, Thomas, Sage & Johnson, 2005). Our data support the view that plasma membrane depolarization promotes senescence through the Rb pathway, as repressed mitotic genes are known E2F targets and the inhibition of Rb prevents senescence induced by plasma membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of E2F transcription factors by Rb is an important pro‐senescence process (Mallette, Goumard, Gaumont‐Leclerc, Moiseeva & Ferbeyre, 2004; Narita et al., 2003; Sebastian, Malik, Thomas, Sage & Johnson, 2005). Our data support the view that plasma membrane depolarization promotes senescence through the Rb pathway, as repressed mitotic genes are known E2F targets and the inhibition of Rb prevents senescence induced by plasma membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPb is translated into two different isoforms: LAP (C/EBPb, p44, p42) and LIP (p20) (Calkhoven et al, 2000;Zahnow, 2009). The LAP:LIP ratio is assumed to regulate cell proliferation through the LAPmediated repression of E2F target genes (Sebastian et al, 2005). Lamb et al (2003) suggested that CCND1 acts similar to LIP by counteracting LAP (C/EBPbeta) functions.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] However, it is now becoming clear that Ras oncogene can also induce senescence via p53-independent pathways such as CCAAT/enhancerbinding protein-b, or ones mediated by p63. 16,17 Apoptosis-stimulating protein of p53 (ASPP) 2 belongs to the evolutionarily conserved ASPP family of proteins that were initially identified through their ability to bind to, and regulate, the apoptotic function of p53 and its family members p63 and p73. 18 Two different ASPP2 transgenic mouse models were generated, expressing either exon 3-or exons 10-17-deleted ASPP2 genes.…”
mentioning
confidence: 99%